Building enterprise information architectures : reengineering information systems - Cook, Melissa A. (Hewlett-Packard professional books, 1996)
In this book, noted expert Melissa A. Cook shows you how to put business management back in charge of processes and information, using easy-to-understand principles that have worked since antiquity. Whether you are an executive manager or a technical professional, you can use these principles to integrate the enterprise with information systems that are more flexible, less complex, less expensive, and fully supportive of your business process reengineering efforts. Building Enterprise Information Architecture is, in short, field guide for taking control of information technology and making it serve your bidding - instead of the other way round